Transitory shocks and long-term human capital accumulation: the impact of conflict on physical health in Peru - Sánchez, Alan (2010)
The recent literature on human capital highlights the importance of investments during the first few years after birth as a determinant of economic outcomes later in life, including labour productivity. This paper assesses the relationship between conflict exposure –a transitory, aggregate, shock– and early nutrition. The relationship between conflict exposure and human capital outcomes can be put into doubt due to the endogenous nature of conflict. In this paper I use a rich dataset that permits me to trace the intensity of a country-specific, large-scale, conflict across regions and over time at the monthly frequency over a 20-year period. I use this data to link conflict exposure prevalent around the time of birth to child-level outcomes of birth cohorts born over an analogous time period. The identification strategy exploits differences in the intensity of exposure between siblings in turn determined by year-month of birth. Results show that, on average, early exposure to conflict did not have an effect on infant mortality but had large negative effects on short-term nutritional outcomes, particularly for the poor. These results suggest that, unless compensatory investments were at place, the Peruvian conflict might have had long-term effects on human capital accumulation through a nutritional channel.